FORMULASI SEDIAAN KRIM ANTI LUKA BAKAR DARI EKSTRAK AIR DAGING DAUN ALOE VERA - P. O. Samirana; N. W. Satriani; P. R. Harfa; S. P. P. Dewi; C. I. S. Arisanti (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2020)
Aloe vera (Aloe vera) is a plant that is empirically often used to heal burns. Aloe vera leaf meat water extract contains saponins and flavonoids, in addition it also contains tannins and polyphenols. This research was conducted to determine whether the extracted water of Aloe vera leaf meat had met the parameters of extract quality standards so that it could be used in formulations. The steps taken are the extraction of aloe vera leaf meat with the method of infundation maceration, standardization of Aloe vera meat water extraction including testing the determination of drying shrinkage, total ash content, determination of ash content which is insoluble in acid, determination of the essence of water soluble extract, determination of the extract soluble in ethanol and chemical screening, identification with FT-IR, preparation of cream preparations, evaluation of cream preparations. Aloe vera leaf meat extract was obtained by infudation technique. Tests for drying drying extract produced 26.33%, total ash content of 1.3%, water soluble extract content of 11.9% and ethanol soluble extract content of 12.01%, total flavonoid content of 2.9%. Keywords: Aloe Vera, Formulation, Cream, Burns.